Reputasi Perusahaan Melalui Islamicity Performance Index (IPI) Pada Lembaga Keuangan Syariah - Ulum, Bachrul (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
The development of sharia financial institutions will be largely determined by the trust of their customers. This is because all financial institutions are required to respond to the reality that fund providers (shareholders and depositors) and other stakeholders have desires. If institutions do not meet their expectations, they will not be willing to provide funds or cooperate well. So Islamic financial institutions must work harder to build trust in their customers. This type of research is a normative approach through library research. The results of this research show that, first, Islamic financial institutions must build a good reputation in order to gain the trust of the wider community based on the identity and image of the institution. The two Islamicity performance index (IPI) can build a good reputation for sharia financial institutions with several indexes used, namely profit sharing ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), Directors-Employee Welfare Ratio (DEWR ), Islamic Income Ratio (IIcR) and Islamic Investment Ratio (IIvR). Keywords: Islamic financial institutions, company reputation, Islamicity performance index